Nasal patency and otorhinolaryngologic-orofacial features in children - Milanesi,Jovana de Moura (2019)
Abstract Introduction: Nasal obstruction is a common symptom in childhood, related to rhinitis and pharyngeal tonsil hypertrophy. In the presence of nasal obstruction, nasal patency may be reduced, and nasal breathing is replaced by mouth breathing. Orofacial and otorhinolaryngologic changes are related to this breathing mode. Objective evaluation of upper airways may be obtained through nasal patency measurement. Objective: To compare nasal patency and otorhinolaryngologic-orofacial features in children. Methods: One hundred and twenty three children, 6-12 year-old, and of both sexes underwent speech therapy evaluation, according to Orofacial Myofunctional Evaluation protocol, clinical and endoscopic otorhinolaryngologic examination and nasal patency measurement, using the absolute and predicted (%) peak nasal inspiratory flow values. Results: Lower values of absolute and estimated peak nasal inspiratory flow values were found in children with restless sleep (p = 0.006 and p = 0.002), nasal obstruction report (p = 0.027 and p = 0.023), runny nose (p = 0.004 and p = 0.012), unsystematic lip closure during mastication (p = 0.040 and p = 0.026), masticatory speed reduced (p = 0.006 and p = 0.008) and altered solid food swallowing (p = 0.006 and p = 0.001). Absolute peak nasal inspiratory flow was lower in children with pale inferior turbinate (p = 0.040), reduced hard palate width (p = 0.037) and altered speech (p = 0.004). Higher absolute values were found in children with increased tongue width (p = 0.027) and, higher absolute and predicted (%) in children with mild everted lip (p = 0.008 and p = 0.000). Conclusions: Nasal patency was lower in children with restless sleep, rhinitis signs and symptoms, hard palate width reduced and with changes in mastication, deglutition and speech functions. It is also emphasized that most of the children presented signs and symptom of allergic rhinitis.